ANALISIS BUTIR SOAL PENILAIAN SUMATIF IPA KELAS VII SMP NEGERI 3 PONTIANAK MENGGUNAKAN ANATES - Hartono, Inayah Dzil Izzati; Tenriawaru, Andi Besse; Ningsih, Kurnia (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
Item analysis is carried out to improve the quality of items through revision or discarding ineffective items. This study aims to determine the quality of items of Summative Assessment of Science Subjects Class VII SMP Negeri 3 Pontianak Academic Year 2022/2023. This research is a quantitative research with descriptive method. Data was obtained through documentation in the form of student answer sheets tested to 135 students with 30 multiple choice questions analyzed in aspects of validity, reliability, difficulty level, and differentiating power using Anates. The results of the analysis using Anates show that the questions have good validity because there are 22 valid items (73%) and 8 invalid items (27%), good reliability with a reliability index of 0.86 categorized as high correlation, the level of difficulty has good quality with questions classified as moderate totaling 19 items (64%), the differentiating power is good with very good categories totaling 4 items (13%), good totaling 15 items (50%) and sufficient totaling 6 items (20%) so that the results of the analysis show that the questions have good quality because they have aspects of validity, reliability, difficulty level and good differentiating power.